Drying Moringa Leaf (Moringa Oliefera) with Dehydrator for Face Mask Formula - Ghaida Gusrinisa; Tri Yuni Hendrawati; Ratri Ariatmi Nugrahani (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2025)
Moringa leaves contain a lot of nutrition and if its powder has a lot of health benefit for our body. Moringa leaf powder can be used as face mask because it contains a lot of good benefit for our skin, for example natural antioxidant. This reasearch is proposed to make moringa leaf powder from fresh moringa leaf and to use the powder as face mask. The purpose of this research are to get the best drying conditions of moringa leaf and the best face mask formula made from moringa. Fresh moringa leaves are dried using food dehydrator at temperature 40, 50, 60, 70 and 80°C and then the powder is analyzed for its protein and vitamin C content. Then, best-dried moringa leaf powder is mixed with another ingredients to make face mask by varying mass of moringa leaf powder used at 5, 10, 15, 20 and 25 g. Furthermore, moringa face mask is analyzed for its pH, drying time and hedonic test. It is found that drying time (y) of moringa leaves decreasing as the temperature of dehydrator increased according to equation y = 0.6429x2 – 5.3571x + 11.9. Average yield of moringa leaves powder is 24.11%; drying temperature 40°C and drying time 7.5 hour get the best-dried moringa leaf powder with protein content of 27.63% and vitamin C content of 1018.02 mg. Proximate analysys of moringa leaf powder resulted in 29.07% protein; 8.72% ash; 7.93% total fat; 8.57% moisture content and 45.73% carbohydrate. Average pH of moringa face mask is 6.44. The drying time of face mask (y) decreasing as the moringa leave powder mass (x) increased according to equation y = -2.343x + 27.227. Face mask with mass percentage 37%(w/w) of moringa leaves powder get the best formula with pH of 6.4, film dryng time of 16.06 minutes and become favorite by hedonic test.